2020
DOI: 10.1016/j.gie.2019.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Blue-light imaging and linked-color imaging improve visualization of Barrett’s neoplasia by nonexpert endoscopists

Abstract: Background and Aims: Endoscopic recognition of early Barrett's neoplasia is challenging. Blue-light imaging (BLI) and linked-color imaging (LCI) may assist endoscopists in appreciation of neoplasia. Our aim was to evaluate BLI and LCI for visualization of Barrett's neoplasia in comparison with white-light endoscopy (WLE) alone, when assessed by nonexpert endoscopists.Methods: In this web-based assessment, corresponding WLE, BLI, and LCI images of 30 neoplastic Barrett's lesions were delineated by 3 expert endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…This result shows that a diagnosis of Barrett's esophagus may be made in the LCI or BLI‐bright mode but missed in the WLI mode. Thus, as with previous studies, LCI or BLI‐bright mode may be superior to WLI mode for the diagnosis of Barrett's esophagus 19‐21 . However, in our study, the BLI‐bright and LCI modes did not increase the concordance rate for the diagnosis of reflux esophagitis and Barrett's esophagus over conventional WLI.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This result shows that a diagnosis of Barrett's esophagus may be made in the LCI or BLI‐bright mode but missed in the WLI mode. Thus, as with previous studies, LCI or BLI‐bright mode may be superior to WLI mode for the diagnosis of Barrett's esophagus 19‐21 . However, in our study, the BLI‐bright and LCI modes did not increase the concordance rate for the diagnosis of reflux esophagitis and Barrett's esophagus over conventional WLI.…”
Section: Discussionsupporting
confidence: 77%
“…BLI uses two monochromatic lasers that help visualize the vascular microarchitecture of the mucosal surface 17,18 . Previous studies have shown that LCI improves the visibility of Barrett's esophagus 19,20 . Other studies have suggested that BLI also assists in the diagnosis of Barrett's esophagus and the detection of esophageal cancer 21‐23 .…”
Section: Introductionmentioning
confidence: 99%
“…81 A cohort study prospectively collected 30 neoplastic BE images captured with WLE, BLI, and LCI reported that the use of BLI and LCI has a significant additional value for the visualization of BE's neoplasia when used by non-expert endoscopists. 82 A new classification system using BLI (BLINC) was proposed for the optimal diagnosis of BE's neoplasia, and BLINC classification has the potential to improve the optical diagnosis of BE's neoplasia with a high degree of sensitivity (96%) and interobserver agreement (κ > 0.8). 83…”
Section: B Barrett's Esophagus and Associated Dysplasia And Adenocarcinomamentioning
confidence: 99%
“…BLI and LCI appear to offer additional value in visualization of Barrett's neoplasia compared to WLE in both expert and non-expert endoscopists. 16,17 iScan with optical enhancement (OE) also appears to offer improved dysplasia detection over WLE, particularly when used with magnification, though did not rise to the level needed to satisfy ASGE PIVI thresholds in a recent trial. 18 Recent guidelines from the ASGE have recommended the use of chromoendoscopy (dye based or virtual) concurrently with Seattle protocol biopsies, as opposed to HDWLE alone with Seattle protocol biopsies.…”
Section: Virtual Chromoendoscopymentioning
confidence: 99%